A high-resolution physical map integrating an anchored chromosome with the BAC physical maps of wheat chromosome 6B - Kobayashi, Fuminori; Wu, Jianzhong; Kanamori, Hiroyuki; Tanaka, Tsuyoshi; Katagiri, Satoshi; Karasawa, Wataru; Kaneko, Satoko; Watanabe, Shota; Sakaguchi, Toyotaka; Hanawa, Yumiko; Fujisawa, Hiroko; Kurita, Kanako; et al. (BMC genomics, 2015)
BACKGROUND: A complete genome sequence is an essential tool for the genetic improvement of wheat. Because the wheat genome is large, highly repetitive and complex due to its allohexaploid nature, the International Wheat Genome Sequencing Consortium (IWGSC) chose a strategy that involves constructing bacterial artificial chromosome (BAC)-based physical maps of individual chromosomes and performing BAC-by-BAC sequencing. Here, we report the construction of a physical map of chromosome 6B with the goal of revealing the structural features of the third largest chromosome in wheat. RESULTS: We assembled 689 informative BAC contigs (hereafter reffered to as contigs) representing 91% of the entire physical length of wheat chromosome 6B. The contigs were integrated into a radiation hybrid (RH) map of chromosome 6B, with one linkage group consisting of 448 loci with 653 markers. The order and direction of 480 contigs, corresponding to 87% of the total length of 6B, were determined. We also characterized the contigs that contained a part of the nucleolus organizer region or centromere based on their positions on the RH map and the assembled BAC clone sequences. Analysis of the virtual gene order along 6B using the information collected for the integrated map revealed the presence of several chromosomal rearrangements, indicating evolutionary events that occurred on chromosome 6B. CONCLUSIONS: We constructed a reliable physical map of chromosome 6B, enabling us to analyze its genomic structure and evolutionary progression. More importantly, the physical map should provide a high-quality and map-based reference sequence that will serve as a resource for wheat chromosome 6B.
Keywords: molekulární evoluce; Physical Chromosome Mapping; chromozomy rostlin; Gene Order; Genetic Markers; Chromosomes, Plant; Triticum; pšenice; genová přestavba; organizátor jadérka; Nucleolus Organizer Region; genetické markery; fyzikální mapování chromozomů; pořadí genů; Chromosomes, Artificial, Bacterial; Gene Rearrangement; umělé bakteriální chromozomy; Evolution, Molecular